Losartan Normalizes Endothelium-Derived Hyperpolarizing Factor-Mediated Relaxation by Activating Ca2+-Activated K+ Channels in Mesenteric Artery From Type 2 Diabetic GK Rat - Takayuki Matsumoto; Keiko Ishida; Kumiko Taguchi; Tsuneo Kobayashi; Katsuo Kamata (Elsevier, 2010)
Ca2+-activated K+ (K Ca ) channels are important for endothelium-derived hyperpolarizing factor (EDHF) signaling. Since treatment with angiotensin II receptor blockers (ARBs) improves vasculopathies in type 2 diabetic patients, we asked whether the EDHF-type relaxation and its associated K Ca channels [small (SK Ca )-, intermediate (IK Ca )-, and large (BK Ca )-conductance channels] are abnormal in mesenteric arteries isolated from Goto-Kakizaki (GK) rats at the chronic stage of type 2 diabetes (34 - 38 weeks) and whether an ARBs (losartan, 25 mg · kg−1 · day−1 for 2 weeks) might correct these abnormalities. Although the acetylcholine chloride-induced EDHF-type relaxation in mesenteric arteries from GK rats was reduced versus the Wistar controls, it was significantly restored by losartan treatment. The SK Ca-blocker apamin or the IK Ca-blocker 1-[(2-chlorophenyl)diphenylmethyl]-1 H-pyrazole (TRAM-34) inhibited such relaxations in the losartan-treated or -untreated Wistar groups and in the losartan-treated GK group, but not in the losartan-untreated GK group. The BK Ca-blocker iberiotoxin had a significant inhibitory effect in only one of these groups, the losartan-treated GK. The relaxations induced by the SK Ca /IK Ca acti-vator NS309 and the BK Ca activator NS1619, which were impaired in GK rats, were normalized by losartan treatment. We conclude that losartan improves EDHF-type relaxation in GK rats at least partly by normalizing SK Ca /IK Ca activities and increasing BK Ca activity. Keywords:: angiotensin receptor antagonist, diabetes, endothelium-derived hyperpolarizing factor (EDHF), GK rat, potassium channel